ANALISIS PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING Studi pada Staff Administrasi Umum dan Keuangan Rumah Sakit Islam Banjarmasin - M. Fajerin Dinata; Ahmad Alim Bachri; Rahmawati (JWM (JURNAL WAWASAN MANAJEMEN), 2018)
This study aims to examine and analyze the influence of leadership style on job satisfaction with organizational commitment as the intervening variable. The object of this research is the staff of general administration and finance of Islam Hospital, Banjannasin. In accordance with the above objectives, in this study four hypotheses have been formulated. The sampling of this research used saturated sample method by using the entire population as the samples. This study used 50 respondents, and all respondents were the staff of general administration and finance of Islam Hospital, Banjarmasin. To facilitate the problem solving, this research was conducted by using regression analysis, path analysis and Sobel Test with the help ofSPSS V.23 The results of this study indicated that leadership style had a positive and significant impact on organizational commitment. Leadership style has a positive and significant effect onjob satisfaction. Organizational commitment had a positive and significant effect on job satisfaction and organizational commitment had positive and significant effect as the intervening variable/mediation between leadership style and job satisfaction